Private Law, Double Distortion Argument, and Property-Owning Democracy - Zanitelli, Leandro Martins (REVISTA QUAESTIO IURIS, 2020)
The article discusses an argument against the use of private law for distributive purposes, Louis Kaplow and Steven Shavell’s double distortion argument (Kaplow and Shavell, 1994). It is sought to ascertain whether one of the theses on which this argument rests, the thesis of equivalence, can be confirmed in the light of John Rawls’s theory of justice. According to the thesis of equivalence, an arrangement constituted by a private law sensitive to distributive justice can be replaced, without loss to justice, by an arrangement containing an efficient private law and measures of taxation and transfer of income to achieve distributive objectives. The paper tests this thesis against two interpretations of the difference, emphasized by Rawls in late writings, between two types of institutional regime, property-owning democracy and welfare state capitalism. The idea is to verify whether an efficient private law (accompanied by taxation and transfer measures) is compatible with property-owning democracy. It is argued that Rawls’s ideas about this type of regime refute the thesis of equivalence, with varying implications depending on how the difference between property-owning democracy and welfare state capitalism is understood.